2018
DOI: 10.1136/gutjnl-2017-315425
|View full text |Cite
|
Sign up to set email alerts
|

Nardilysin inhibits pancreatitis and suppresses pancreatic ductal adenocarcinoma initiation in mice

Abstract: Nrdc inhibits pancreatitis and suppresses PDA initiation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…showing that pancreatic deletion of NRDC in Kras G12D -driven mice promoted PDAC tumorigenesis, and considering the absence of NRDC expression in a subset of human PDAC 43 , the metastasis observed in Plk3-knockout mice might be attributed to deficient NRDC-mediated cleavage on Plk3 in PDAC cells. Our data suggest that, in addition to its reduced expression level, Plk3 in PDAC cells is more resistant to NRDCmediated cleavage into activated p41Plk3, conferring PDAC cells with apoptosis resistance, contributing to their progression towards malignancy and metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…showing that pancreatic deletion of NRDC in Kras G12D -driven mice promoted PDAC tumorigenesis, and considering the absence of NRDC expression in a subset of human PDAC 43 , the metastasis observed in Plk3-knockout mice might be attributed to deficient NRDC-mediated cleavage on Plk3 in PDAC cells. Our data suggest that, in addition to its reduced expression level, Plk3 in PDAC cells is more resistant to NRDCmediated cleavage into activated p41Plk3, conferring PDAC cells with apoptosis resistance, contributing to their progression towards malignancy and metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…We demonstrated that deleting Plk3 in p48-cre;Kras LSL- G12D mice inhibited caspase-3 activation. Linking a study from Ikuta et al that pancreatic deletion of NRDC in Kras G12D -driven mice promoted PDAC tumorigenesis and NRDC expression is absent in a subset of human PDAC (Ikuta et al, 2019), metastasis in Plk3 knockout mice was correlated to deficient NRDC-mediated cleavage on Plk3 to induce anoikis in PDAC cells. Based on our data, in addition to reduced expression level, Plk3 in PDAC cells are more resistant to NRDC-mediated cleavage to generate activated p41Plk3, bestowing PDAC cells to develop anoikis resistance, to progress towards malignancy and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sometimes it is difficult for clinicians and pathologists to distinguish between distal cholangiocarcinoma and pancreatic head cancer, so NRDC may play a potential role in identifying them. Moreover, there are still some reports indicating that deletion of NRDC in the mice’s pancreas dramatically leads to spontaneous chronic pancreatitis and accelerates KRAS-driven pancreatic tumorigenesis [ 19 ], demonstrating that NRDC may play a kind of tumor-suppressive function and be an essential factor in the growth in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…NRDC has also been found in the mitochondria [ 16 ], cytoplasm [ 17 ], and nucleus [ 18 ] which suggests that it might participate in some important signaling pathways. Meanwhile, a report revealed that when NRDC is knocked out in mice, it leads to spontaneous chronic pancreatitis, diabetes, and the stimulation of pancreatic ductal adenocarcinoma initiation [ 19 ]. Hence, in order to determine the role of NRDC in pancreatic ductal adenocarcinoma, we designed an observational cohort study to determine the clinical value of NRDC.…”
Section: Introductionmentioning
confidence: 99%